PRODUCTION OF WHITE SHRIMP Litopenaeus vannamei IN FLOATING CAGE SYSTEM WITH DIFFERENT STOCKING DENSITY AT THOUSAND ISLAND STRAIT - Sophia N.M. Fendjalang; Tatag Budiardi; Eddy Supriyono; Irzal Effendi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
The aim of this study was to analyze the survival rate, growth, and haemolymp glucose level of white shrimp as a physiological responses at floating cage cultured on different stock den-sity, in Seribu Islands Strait. White shrimp used in this study contained approximate weight of 1.0±0.06 g and length of 5.0±0.03 cm from Nusa Karamba Hatchery in Seribu Island. White shrimp was maintained in 90 days, feed with ±36.28 % protein content 4 times each day with feeding rate (FR) of 7%. Water qualities and shrimp growth measurements was conducted every 10 days. Haemolymph glucose sam-pling was performed in the beginning and at the end of the experiment. Result showed that treatment with stock densituy of 250 shrimp/m2 had a better survival rate of 30.33% and feed conversion ratio of 1.13 than other treatments. Phy-siological response in the form of glucose hemolim also showed a better response in the 250 ind./m2 stock density of 41.87 mg/dl indicating that the white shrimp did not experience a sig-nificant stress. Keywords: Litopenaeus vannamei,  sea floating cages, stock density, strait waters, Seribu Islands.